Exertional heat illness: adoption of policies and influencing contextual factors as reported by athletic administrators - Scarneo-Miller, Samantha E.; Adams, William M.; Coleman, Kelly A.; Lopez, Rebecca M. (Sports Health, 2023)
Background:Little is known about the adoption by athletic administrators (AAs) of exertional heat illness (EHI) policies, and the corresponding facilitators and barriers of such policies within high school athletics. This study describes the adoption of comprehensive EHI policies by high school AAs and explores factors influencing EHI policy adoption.Hypothesis:We hypothesized that <50% of AAs would report adoption of an EHI policy, and that the most common facilitator would be access to an athletic trainer (AT), whereas the most common barrier would be financial limitations.Study Design:Cross-sectional.Level of Evidence:Level 4.Methods:A total of 466 AAs (82.4% male; age, 48 ± 9 years) completed a validated online survey to assess EHI prevention and treatment policy adoption (11 components), as well as facilitators and barriers to policy implementation. Access to athletic training services was ascertained by matching the participants? zip codes with the Athletic Training Locations and Services Project. Policy adoption, facilitators, and barriers data are presented as summary statistics (proportions, interquartile range (IQR)). A Welch t test evaluated the association between access to athletic training services and EHI policy adoption.Results:Of the AAs surveyed, 77.9% (n = 363) reported adopting a written EHI policy. The median of EHI policy components adopted was 5 (IQR = 1,7), with only 5.6% (n = 26) of AAs reporting adoption of all policy components. AAs who had access to an AT (P = 0.04) were more likely to adopt a greater number of EHI-related policies, compared with those without access to an AT. An AT employed at the school was the most frequently reported facilitator (36.9%).Conclusion:Most AAs reported having written EHI policy components, and access to an AT resulted in a more comprehensive policy.Clinical Relevance:Employment of an AT within high school athletics may serve as a vital component in facilitating the adoption of comprehensive EHI policies.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

National Trends in Athletic Training Service Provision in U.S. High Schools: A Five-Year Longitudinal Assessment - Kim, D; Eason, Christianne; Grubb, Joseph; Casa, Douglas; Coleman, Kelly; Filep, Erica; Huggins, Robert (Current Sports Medicine Reports, 2026)
Keywords: Athletes; Athletic training; Sports medicine; Trainer; Training (meteorology); dept.hms

Athletic training employment in secondary schools by geographic setting and school size within the United States. - Suzuki-Yamanaka, Miwako; Huggins, Robert A.; Armstrong, Kirk J.; Coleman, Kelly A.; Casa, Douglas J.; Kaneoka, Koji (Journal of athletic training, 2021)
Context: The Athletic Training Locations and Services (ATLAS) Annual Report suggested that athletic trainer (AT) employment status differed based on geographic locale. However, the influence of geographic locale and school size on AT employment is unknown. Objective: To determine if differences existed in the odds of having AT services by locale for public and private schools and by student enrollment for public schools. Design: Cross-sectional study. Setting: Public and private secondary schools with athletics programs. Patients or Other Participants: Data from 20 078 US public and private secondary schools were obtained. Main Outcome Measures(s): Data were collected by the ATLAS Project. Athletic trainer employment status, locale (city, suburban, town, or rural) for public and private schools, and school size category (large, moderate, medium, or small) only for public schools were obtained. The employment status of ATs was examined for each category using odds ratios. Logistic regression analysis produced a prediction model. Results: Of the 19 918 public and private schools with available AT employment status and locale, suburban schools had the highest access to AT services (80.1%) with increased odds compared with rural schools (odds ratio = 3.55 [95% CI = 3.28, 3.85]). Of 15 850 public schools with known AT employment status and student enrollment, large schools had the highest rate of AT services (92.1%) with nearly 18.5 times greater odds (odds ratio = 18.49 [95% CI = 16.20, 21.08]) versus small schools. The logistic model demonstrated that the odds of access to an AT increased by 2.883 times as the school size went up by 1 category. Conclusions: Nationally, suburban schools and large public schools had the greatest access to AT services compared with schools that were in more remote areas and with lower student enrollment. These findings elucidate the geographic locales and student enrollment levels with the highest prevalence of AT services. Ó by the National Athletic Trainers’ Association, Inc
1 citations (Crossref) [2023-10-31] https://www.ncbi.nlm.nih.gov/pubmed/33480996 ; https://pubmed.ncbi.nlm.nih.gov/33480996/ ; https://meridian.allenpress.com/jat/article/56/9/1010/451538/Athletic-Training-Employment-in-US-Secondary ; https://europepmc.org/article/MED/33480996
Keywords: adult; article; athletic trainer; athletics; controlled study; cross-sectional study; dept.hms; employment status; female; high school; human; male; outcome assessment; peer-reviewed; prediction; prevalence; training

Spinal cord injury management policies in high school sports as reported by athletic administrators - Scarneo-Miller, Samantha E.; Swartz, Erik E.; Register-Mihalik, Johna K.; Coleman, Kelly A.; Emrich, Christina M.; DiStefano, Lindsay J. (Translational Journal of the American College of Sports Medicine, 2024)
Introduction/Purpose Athletic administrators (AA) in U.S. high schools are uniquely positioned to provide guidance and endorsement for the prevention and management of common sport-related catastrophic injuries, such as the development of a spinal cord injury management (SCIM) policy. The purpose of this project was to evaluate AA’s knowledge of comprehensive SCIM policies in U.S. high schools. Secondarily, we aimed to investigate the factors, facilitators, and barriers to the development and adoption of comprehensive policies. Methods An online questionnaire was distributed to 6423 AA working in U.S.-based high school athletics, with 366 included in the final data analysis. The questionnaire evaluated AA’s knowledge of comprehensive SCIM policies addressing components of adoption, documentation, and communication. The questionnaire was developed based on the 2002 “National Athletic Trainers’ Association Position Statement: Acute Management of the Cervical Spine-Injured Athlete.” The questionnaire also inquired about facilitators and barriers to developing and adopting comprehensive policies. Proportions were calculated for policy adoption, and independent-samples t-tests evaluated the influence of athletic training services on comprehensive SCIM policies. Results About half of AA (49.2%, n = 180/366) reported having all recommended components of a written SCIM policy. AA who had access to an athletic trainer (yes = 62.9%, no = 18.1%, unknown = 19%) were more likely to have a comprehensive SCIM policy compared with those without access (80.6% vs 19.4%, χ21 = 7.091, P = 0.008, prevalence ratio = 1.24, 95% confidence interval = 1.03–1.50). The most commonly reported facilitator (49.9%) was “having a medical professional at the school,” and the main barrier (30.2%) was “my school would need more information, resources, assistance, etc.” Conclusions The findings identify areas for improvement in supporting the health and safety of children in high school participating in interscholastic athletics. Future dissemination and implementation research should develop strategies tailored to individual school community and need to improve SCIM policy adoption and implementation.
Keywords: dept.hms

Athletic Training Services Trends Between Public and Private High Schools: A 5-Year Retrospective Analysis - Kim, Donghyeon; Defino, Amir; Eason, Christianne; Casa, Douglas; Yoo, Chaeyeon; Yoshihara, Ayami; Coleman, Kelly; Filep, Erica; Huggins, Robert (Journal of Athletic Training, 2025)
Context Access to athletic trainers (ATs) in high schools is crucial for student-athlete (SA) safety. Although most high schools in the United States have access to athletic training services (ATS), no authors have longitudinally compared ATS trends between public (PUB) and private (PVT) school sectors. Objective To compare ATS trends between PUB and PVT schools from the 2018–2019 through 2022–2023 academic years. Design Longitudinal cross-sectional study. Setting Online survey. Main Outcome Measure(s) High school responses to the Athletic Training Locations and Services survey from all 50 US states and the District of Columbia were queried from the 2018–2019 to 2022–2023 academic years. Average numbers of SAs ( SAs ), sports ( Sports ), full-time ATs ( FtATs ), part-time ATs ( PtATs ), and the sum of full-time and part-time ATs ( ATs ), along with the average weekly contracted hours ( CHrs ) and actual hours ( AHrs ) per school, and ratios of SAs : ATs , Sports : ATs , CHrs : SAs , CHrs : Sports , AHrs : SAs , and AHrs : Sports were examined to track ATS trends over 5 years and compare PUB vs PVT schools. Results Public schools had higher SAs and Sports vs PVT schools (both P < .001). Private schools had higher ATs , CHrs , and AHrs than PUB schools (all P < .050). Ratios of SAs : ATs and Sports : ATs were higher in PUB schools, whereas CHrs : SAs , AHrs : SAs , CHrs : Sports , and AHrs : Sports were higher in PVT schools (all P < .050). From 2018–2019 to 2022–2023, PUB schools increased Sports and Sports : ATs ; PVT schools increased SAs , Sports , ATs , and SAs : ATs (all P < .050). Over the years, PUB schools decreased CHrs : Sports and AHrs : Sports ; PVT decreased CHrs : SAs , AHrs : SAs , CHrs : Sports , and AHrs : Sports . FtATs increased in both sectors, whereas PtATs decreased in only PVT schools. Conclusions Overall, ATS were more extensively provided in PVT schools, based on ATs and ATS hours. Both sectors increased FtATs , which is encouraging. However, as SAs and Sports increased, ATS provided per SA and sport declined.
Keywords: Athletes; Athletic training; Context (archaeology); MEDLINE; Private sector; Training (meteorology); athletes; dept.hms; safety; sports; student health services

Combining MRI and cognitive evaluation to classify concussion in university athletes - Ly, Monica T.; Scarneo-Miller, Samantha E.; Lepley, Adam S.; Coleman, Kelly; Hirschhorn, Rebecca; Yeargin, Susan; Casa, Douglas J.; Chen, Chi-Ming (Brain Imaging and Behavior, 2022)
Current methods of concussion assessment lack the objectivity and reliability to detect neurological injury. This multi-site study uses combinations of neuroimaging (diffusion tensor imaging and resting state functional MRI) and cognitive measures to train algorithms to detect the presence of concussion in university athletes. Athletes (29 concussed, 48 controls) completed symptom reports, brief cognitive evaluation, and MRI within 72 h of injury. Hierarchical linear regression compared groups on cognitive and neuroimaging measures while controlling for sex and data collection site. Logistic regression and support vector machine models were trained using cognitive and neuroimaging measures and evaluated for overall accuracy, sensitivity, and specificity. Concussed athletes reported greater symptoms than controls (∆R2 = 0.32, p < .001), and performed worse on tests of concentration (∆R2 = 0.07, p < .05) and delayed memory (∆R2 = 0.17, p < .001). Concussed athletes showed lower functional connectivity within the frontoparietal and primary visual networks (p < .05), but did not differ on mean diffusivity and fractional anisotropy. Of the cognitive measures, classifiers trained using delayed memory yielded the best performance with overall accuracy of 71%, though sensitivity was poor at 46%. Of the neuroimaging measures, classifiers trained using mean diffusivity yielded similar accuracy. Combining cognitive measures with mean diffusivity increased overall accuracy to 74% and sensitivity to 64%, comparable to the sensitivity of symptom report. Trained algorithms incorporating both MRI and cognitive performance variables can reliably detect common neurobiological sequelae of acute concussion. The integration of multi-modal data can serve as an objective, reliable tool in the assessment and diagnosis of concussion.
0 citations (Crossref) [2023-10-31]
Keywords: Classification; Concussion; Diffusion tensor imaging (DTI); Mild traumatic brain injury (mTBI); Resting state functional MRI; dept.hms; peer-reviewed